Penyuluhan Dampak Pernikahan Dini Terhadap Kesehatan Reproduksi Di SMA Etislandia Medan - Hudeni Rizki; Dealita Khairani Daulay; Evlindari Sentani Daulay (STIKES Columbia Asia Medan, 2026)
Early marriage remains a significant issue in Indonesia, particularly among adolescents, and has serious implications for reproductive health. This community service activity aimed to increase students' knowledge about the impact of early marriage on reproductive health. The activity was conducted at Etislandia Senior High School Medan with 43 participating students. The method used was counseling through lectures, discussions, and question-and-answer sessions, accompanied by pre-test and post-test evaluations. The results showed a significant increase in students' knowledge, with the average pre-test score of 54.2 rising to 85.6 in the post-test. Students showed high enthusiasm during the session and were able to identify various risks of early marriage, including reproductive tract infections, cervical cancer risk, and maternal mortality. This activity has implications for the importance of reproductive health education as a preventive effort against early marriage